KTN80 confers precision to microtubule severing by specific targeting of katanin complexes in plant cells. (4th October 2017) - Wang, Chaofeng; Liu, Weiwei; Wang, Guangda; Li, Jun; Dong, Li; Han, Libo; Wang, Qi; Tian, Juan; Yu, Yanjun; Gao, Caixia; Kong, Zhaosheng
Abstract: The microtubule (MT)‐severing enzyme katanin triggers dynamic reorientation of cortical MT arrays that play crucial functions during plant cell morphogenesis, such as cell elongation, cell wall biosynthesis, and hormonal signaling. MT severing specifically occurs at crossover or branching nucleation sites in living Arabidopsis cells. This differs from the random severing observed along the entire length of single MTs in vitro and strongly suggests that a precise control mechanism must exist in vivo . However, how katanin senses and cleaves at MT crossover and branching nucleation sites in vivo has remained unknown. Here, we show that the katanin p80 subunit KTN80 confers precision to MT severing by specific targeting of the katanin p60 subunit KTN1 to MT cleavage sites and that KTN1 is required for oligomerization of functional KTN80–KTN1 complexes that catalyze severing. Moreover, our findings suggest that the katanin complex in Arabidopsis is composed of a hexamer of KTN1–KTN80 heterodimers that sense MT geometry to confer precise MT severing. Our findings shed light on the precise control mechanism of MT severing in plant cells, which may be relevant for other eukaryotes. Synopsis: The Arabidopsis thaliana katanin p80 subunit KTN80 plays a crucial role in defining the site of microtubule severing by precisely targeting katanin complex to microtubule crossover and branching nucleation sites. Four KTN80 isoforms act redundantly to sever microtubules at crossover and branching nucleation sites. KTN80 targets the katanin p60 subunit KTN1 to microtubules. KTN1 is dispensable for KTN80 recruitment to microtubules. KTN1 is required for hexamerisation of KTN1–KTN80 heterodimers to form an active katanin complex. Abstract : Microtubule‐severing complex katanin is guided to crossover and branching nucleation sites by subunit p80, which in turn recruits the catalytic subunit p60.